Insights Into Modern Undergraduate Ultrasound Education: Prospective Comparison of Digital and Analog Teaching Resources in a Flipped Classroom Concept – The DIvAN Study - Weimer, Johannes M.; Recker, Florian; Horn, Leonie; Kuenzel, Julian; Dirks, Klaus; Ille, Carlotta; Buggenhagen, Holger; Börner, Norbert; Weimer, Andreas Michael; Vieth, Thomas; Lorenz, Liv; Rink, Maximilian; Merkel, Daniel; Dionysopoulou, Anna; Ludwig, Michael; Kloeckner, Roman; Weinmann-Menke, Julia; Müller, Lukas (Ultrasound International Open, 2024)
Purpose  Sonography training has become an important part of university medicine courses. This study explores the impact of digital and analog teaching resources on learning outcomes, knowledge retention, and student preferences and motivation in a flipped classroom setting.Materials and Methods  This prospective controlled study involving two groups of third-year medical students included a voluntary three-day compact ultrasound course given in a flipped classroom, comprising 26 teaching units of 45 minutes each. Hardcopy lecture notes (control group) and E-learning (study group) were used as teaching resources. Evaluations were conducted before (pre) and during the preparation phase (intermediate), and after (post) the face-to-face course. Likert scale responses, written theory tests with very short answer questions (Theorypre, Theoryinter, Theorypost), and practical examinations (Practiceinter, Practicepost) were used for student self-assessment and to measure attitude, motivation, as well as theoretical and practical skills.Results  A total of N=236 complete data sets (study group n=136; control group n=100) were analyzed. Both groups showed an equivalent initial level of, and a continuous and significant (p<0.01) increase in, subjective and objective skills over the evaluated time frame. The study group achieved significantly (p<0.05) better results in Theoryinter, Theorypost, Practiceinter, and Practicepost. The study group evaluated their teaching resource and the training concept significantly (p<0.05) better.Conclusion  The integration of digital resources into sonography education provides comparable learning outcomes to traditional analog materials, enhancing the preparatory phase. In the future, digitally supported training should be used more.
Keywords: ultrasound education; blended learning; flipped classroom; E-Learning; ultrasound training